Current understanding of eryptosis: mechanisms, physiological functions, role in disease, pharmacological applications, and nomenclature recommendations - Tkachenko, Anton; Alfhili, Mohammad A; Alsughayyir, Jawaher; Attanzio, Alessandro; Al Mamun Bhuyan, Abdulla; Bukowska, Bożena; Cilla, Antonio; Quintanar-Escorza, Martha A; Föller, Michael; Havranek, Ondrej; Jilani, Kashif; Onishchenko, Anatolii; et al. (Cell death & disease, 2025)
Early studies have shown that erythrocytes have caspase-3 and caspase-8 and are capable of dying through an apoptotic-like cell death triggered by Ca2+ ionophores. This cell death is associated with apoptosis-like morphological signs, including cell shrinkage, membrane blebbing, and phosphatidylserine externalization. To emphasize that mature erythrocytes don't have the apoptotic mitochondrial machinery and distinguish this unique cell death modality from apoptosis, it was named "eryptosis". Over recent decades, our knowledge of eryptosis has been significantly expanded, providing more insights into the uniqueness of cell death pathways in erythrocytes. In this review, we aim to summarize our current understanding of eryptosis, formulate the nomenclature and guidelines to interpret results of eryptosis studies, provide a synopsis of morphological and biochemical features of eryptosis, and highlight the role of eryptosis in health and disease, including its druggability.
Keywords: erytrocyty; terminologie jako téma; Calcium; apoptóza; Terminology as Topic; vápník; Animals; Humans; eryptóza; lidé; Eryptosis; zvířata; Apoptosis; Erythrocytes